Educational and Outreach Initiatives to Support Community-Based Waste Management for a Sustainable Environment in Dech Charoen Village, Thailand - Aktawan, Agus; Rahayu, Aster; Biddinika, Muhammad Kunta; Hakika, Dhias Cahya; Areeprasert, Chinnathan (Indonesia Berdaya, 2025)
The rapid rise in urbanization and waste production has significantly impacted the environment. Therefore, community-based waste management is a crucial approach for reducing the environmental impact of domestic and household waste. This community service project aims to promote environmental sustainability through community-based education on waste management. This initiative was carried out in Dech Charoen Village, Thailand, aiming to increase community awareness about the importance of sustainable waste management practices. This paper discusses the community service activities conducted in Dech Charoen Village and their impact on community empowerment and environmental sustainability. The activities included a sharing session on community-based waste management, outreach on the reduce, reuse, and recycle (3R) principle for inorganic waste, and practical outreach on processing organic waste using a composting machine. Results showed a considerable rise in awareness of waste management methods, with more than 90% of participants achieving a better understanding of waste segregation, recycling, composting practices, and the importance of community involvement.